2017
DOI: 10.1021/acschembio.6b00998
|View full text |Cite
|
Sign up to set email alerts
|

Hepta-Mutant Staphylococcus aureus Sortase A (SrtA7m) as a Tool for in Vivo Protein Labeling in Caenorhabditis elegans

Abstract: In vivo protein ligation is of emerging interest as a means of endowing proteins with new properties in a controlled fashion. Tools to site-specifically and covalently modify proteins with small molecules, peptides, or other proteins in living cells are few and far between. Here, we describe the development of a Staphylococcus aureus sortase (SrtA)-based protein ligation approach for site-specific conjugation of fluorescent dyes and ubiquitin (Ub) to modify proteins in Caenorhabditis elegans. Hepta-mutant SrtA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…An analysis of degradation kinetics for two in situ-tagged targets, GFP::MAD-1 and GFP:: PP1 , in the embryonic intestine revealed that GFP::MAD-1 was degraded with a half-life of ∼6 min, whereas GFP::PP1 GSP-2 , which is more abundant and cytoplasmic/nucleolar rather than nuclear, was degraded with an ∼40 min half-life. These degradation rates are comparable with rates published previously for ZF1 degron-tagged fusions targeted by ZIF-1 expression (15-30 min half-life; Armenti et al, 2014), auxin-inducible degradation (∼20 min half-life; Zhang et al, 2015) and sortase-based F-box ligation-mediated degradation (∼1 h half-life; Wu et al, 2017). Thus, degradation rates will differ between targets depending on abundance and accessibility, but are likely to be comparable for the different methods.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…An analysis of degradation kinetics for two in situ-tagged targets, GFP::MAD-1 and GFP:: PP1 , in the embryonic intestine revealed that GFP::MAD-1 was degraded with a half-life of ∼6 min, whereas GFP::PP1 GSP-2 , which is more abundant and cytoplasmic/nucleolar rather than nuclear, was degraded with an ∼40 min half-life. These degradation rates are comparable with rates published previously for ZF1 degron-tagged fusions targeted by ZIF-1 expression (15-30 min half-life; Armenti et al, 2014), auxin-inducible degradation (∼20 min half-life; Zhang et al, 2015) and sortase-based F-box ligation-mediated degradation (∼1 h half-life; Wu et al, 2017). Thus, degradation rates will differ between targets depending on abundance and accessibility, but are likely to be comparable for the different methods.…”
Section: Discussionsupporting
confidence: 86%
“…Of the described methods for conditional protein degradation in C. elegans (this report; Armenti et al, 2014;Wu et al, 2017;Zhang et al, 2015), each has advantages and limitations. The auxininducible degron enables simultaneous spatial (via tissue-specific expression of the TIR1 adaptor) and temporal (timing of auxin addition) control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ease of editing the C. elegans genome using CRISPR/Cas9-based approaches 564 (Calarco and Friedland 2015) and heterologous gene manipulation tools is ushering in a 565 new era of cellular and developmental biology. Several new tools available to C. elegans 566 researchers require the insertion of small amino acid tags into target loci, including ZF1 567 tagging (Armenti et al 2014), sortase A (Wu et al 2017), and the AID system (Zhang et 568 al. 2015).…”
Section: Conclusion 563mentioning
confidence: 99%
“…Caenorhabditis elegans, including ZF1 tagging (Armenti et al 2014), a GFP nanobody 70 approach (Wang et al 2017), sortase A (Wu et al 2017), and auxin-mediated degradation 71 (Zhang et al 2015). 72…”
Section: Introduction 62 63mentioning
confidence: 99%